Study on the Chinese Anostostomatidae (Orthoptera: Ensifera) X: New descriptions of Anabropsis (Pseudapteranabropsis) Pang, Lu & Bian, 2023 from Guangxi - Pang, Siyu; Yang, Ruigang; Bian, Xun (Zootaxa, 2024)
The paper reports the male sex of Anabropsis (Pseudapteranabropsis) flavimaculata Pang, Lu & Bian, 2023 and one new species Anabropsis (Pseudapteranabropsis) bifurcata sp. nov. from Guangxi, China. All the specimens are deposited in Guangxi Normal University.